HUBUNGAN KARAKTERISTIK IBU BALITA DENGAN PEMANFAATAN DATA KARTU MENUJU SEHAT (KMS) DALAM BUKU KIA (STUDI KASUS PUSKESMAS KEDUNGMUNDU KOTA SEMARANG TAHUN 2016) - Ana Putri Rahayu; Yudhy Dharmawan; Djoko Nugroho (Jurnal Kesehatan Masyarakat (Undip), 2018)
Toddler growth monitoring is used to determine the underweight growth status based on weight weighing and to follow up any growth disturbance cases through KMS. KMS data to be an effective and fast media for health workers to know what health services that have been obtained by toddlers. According to BPB 2014 data, approximately 78.5% of under-five mothers in Kedungmundu Health Center do not carry KMS books when weighing or checking their children's health. And according to preliminary study results through interviews with Nutrition program holders and KIA in Kedungmundu Health Center almost 70% of underfive mother can not read KMS data in KIA Book correctly. The purpose of this research is to know the relationship of the characteristics of under-five mother with the utilization of Health Card Toward Data (KMS) in KIA book (case study at Puskesmas Kedungmundu Kota Semarang 2016). The population in this research is 68 mother under five with the inclusion criteria desired by the researcher to be used as research sample. While the sample in this study is the total population. Data analysis used is Rank Spearman correlation by using value of ρs. The result of the research shows that the age of the youngest child is 20 years old and the age of the oldest mother is 40 years old, the highest education percentage of the mother is the advanced education (75,0%), the majority of mother work is housewife (not working) %). The result of statistic test found that there is correlation between very low correlation between the age of the under-five mother (ρs = 0,101) and the education of the under-five mother (ρs = 0,105), there is correlation with the weak correlation between mother job (ρs = 0,166), knowledge of mother of toddler (ρs = 0.287) and the attitude of the infant (ρs = 0,285) with the use of KMS data in the KIA book. Suggested to Puskesmas Kedungmundu can provide information or counseling to mother of toddler about the importance of utilizing KMS data in KIA book related to early detection of infant growth disorder by using KMS data through activity done in community such as posyandu activity, PKK meeting or in study group.